Análise de convergência espacial do setor agropecuário no estado de São Paulo - Paula, Laiana de Oliveira (Universidade Federal de São Carlos, 2022)
According to the Institute of Agricultural Economics, the agricultural sector is the main activity in 260 municipalities in São Paulo (BEZERRA et al, 2005). This work aims to identify whether the disparity in the value added of the agricultural sector decreased between 2002 and 2019 in the municipalities of the state of São Paulo. Initially, Exploratory Spatial Data Analysis (AEDE) is used, based on Moran's I statistic to show patterns of spatial association, and through the local indicator of spatial association (LISA) with the identification of clusters. Finally, the regression of β-convergence was carried out in order to identify whether the values are converging on the average, that is, if the municipalities with the lowest value added per capita in the agricultural sector show greater growth in relation to the municipalities with the highest value. added per capita of the agricultural sector, as identified in the β-convergence studies present in the literature. As a result, the work observes, through Moran's I, the presence of a positive spatial association of the agricultural sector between the municipalities. The Moran Local (LISA) statistic showed the incidence of three clusters of HH group (high value of the agricultural sector with similar neighbors) and one LL group (municipalities with low value of the agricultural sector with similar neighbors). In the end, the absolute β-convergence regression indicates a negative value of the β coefficient, demonstrating that the higher the initial agricultural value added, the lower the growth of value added in the agricultural sector in the study period.
Analysis of spatial convergence of the agricultural sector in the state of São Paulo
Keywords: Convergência-β; Setor agropecuário; Análise exploratória de dados espaciais; β-convergence; Agricultural sector; Exploratory analysis of spatial data; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA REGIONAL E URBANA